2012
DOI: 10.1371/journal.pgen.1002629
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Scans Identify Differentially Methylated Regions for Age and Age-Related Phenotypes in a Healthy Ageing Population

Abstract: Age-related changes in DNA methylation have been implicated in cellular senescence and longevity, yet the causes and functional consequences of these variants remain unclear. To elucidate the role of age-related epigenetic changes in healthy ageing and potential longevity, we tested for association between whole-blood DNA methylation patterns in 172 female twins aged 32 to 80 with age and age-related phenotypes. Twin-based DNA methylation levels at 26,690 CpG-sites showed evidence for mean genome-wide heritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
566
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 624 publications
(623 citation statements)
references
References 55 publications
(85 reference statements)
44
566
11
2
Order By: Relevance
“…Some evidence show that age-related hypermethylation are more conserved across different tissues than hypomethylation [5,26]. However, we only studied blood samples and adjusted methylation data using estimated cellular compositions [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence show that age-related hypermethylation are more conserved across different tissues than hypomethylation [5,26]. However, we only studied blood samples and adjusted methylation data using estimated cellular compositions [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that age-related methylation alterations depend on genetic effects [9], and another recent study on mother-children pairs reported that meQTL associations were stable over time [12]. Twin studies of the epigenome have been used to estimate methylation heritability [9,13], and higher methylation correlation has been observed in monozygotic (MZ) than dizygotic (DZ) twin pairs [5,14]. However, the change of intra-twin-pair methylation difference over time has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The eQTL analysis revealed that this region also affects the expression of the WRD55 and ARL4A genes, primarily in brain tissue. Epigenetic changes in ARL4A have previously been found to associate with maternal longevity in an epigenome‐wide association study of age and age‐related phenotypes (Bell et al ., 2012), indicating a possible link between the 5q31.3 deletion and longevity.…”
Section: Discussionmentioning
confidence: 99%
“…In both humans and domesticated animals, there is vast literature characterizing genes or genomic regions that either become hyper‐ or hypomethylated with age (Bollati et al., 2009; Christensen et al., 2009; Bell et al., 2012; Gryzinska, Blaszczak, Strachecka, & Jezewska‐Witkowska, 2013; Gryzinska et al., 2016; Spiers et al., 2016). In wild animals, there is growing interest in age‐specific DNA methylation (Paoli‐Iseppi et al., 2017), but few studies have examined this and the results are often contradictory.…”
Section: Discussionmentioning
confidence: 99%